Space Security - Martínek, Patrik; Dubský, Zbyněk, 1974-; Eichler, Jan, 1952-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
This paper examines the security of the outer space with regards to the evolving legal framework in recent years and the efforts by dominant state actors that appear to be trying to enforce their interests at the expanse of the international community. As a result, there is a growing tension among the three main actors of this area. The United States are being challenged by Russia and China and the development of new counter-space technologies is stirring up a security dilemma. The first part of this paper introduces the concept of space security. The second part introduces the main actors, describes the evolvement of the legal framework and deals with the currently most debated topics concerning the future development of the use of outer space. Since the United States have a pre-eminent role, the third part of this paper focuses primarily on conducting a discourse analysis of the past nine years of the context of the political statements and proclamations of the U.S. officials regarding the issues of “space security”.
Vedoucí práce: Zbyněk Dubský
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: mezinárodní studia - diplomacie [obor bakal. práce]; bakalářské práce; bachelor's theses